SOCIO-PSYCHOLOGICAL PORTRAIT OF MODERN FATHERS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In the article, who is a father, who is a modern father, the term "big father", the formation of an internal father figure, the breadwinner, the head of the family, children rely on, follow, trust and are proud of their father. The modern father has a more difficult and long way to go.